Factors Predictive of Prolonged Postoperative Narcotic Usage Following Orthopaedic Surgery. Issue 6 (June 2020) - Lavoie-Gagne, Ophelie; Nwachukwu, Benedict U.; Allen, Answorth A.; Leroux, Timothy; Lu, Yining; Forsythe, Brian
Abstract : Background: The purpose of this comprehensive review was to investigate risk factors associated with prolonged opioid use after orthopaedic procedures. A comprehensive review of the opioid literature may help to better guide preoperative management of expectations as well as opioid-prescribing practices. Methods: A systematic review of all studies pertaining to opioid use in relation to orthopaedic procedures was conducted using the MEDLINE, Embase, and CINAHL databases. Data from studies reporting on postoperative opioid use at various time points were collected. Opioid use and risk of prolonged opioid use were subcategorized by subspecialty, and aggregate data for each category were calculated. Results: There were a total of 1, 445 eligible studies, of which 45 met inclusion criteria. Subspecialties included joint arthroplasty, spine, trauma, sports, and hand surgery. A total of 458, 993 patients were included, including 353, 330 (77%) prolonged postoperative opioid users and 105, 663 (23%) non-opioid users. Factors associated with prolonged postoperative opioid use among all evaluated studies included body mass index (BMI) of ≥40 kg/m 2 (relative risk [RR], 1.06 to 2.32), prior substance abuse (RR, 1.08 to 3.59), prior use of other medications (RR, 1.01 to 1.46), psychiatric comorbidities (RR, 1.08 to 1.54), and chronic pain conditions including chronic back pain (RR, 1.01 to 10.90), fibromyalgia (RR, 1.01 to 2.30), and migraines (RR, 1.01 to 5.11). Age cohorts associated with a decreased risk of prolonged postoperative opioid use were those ≥31 years of age for hand procedures (RR, 0.47 to 0.94), ≥50 years of age for total hip arthroplasty (RR, 0.70 to 0.80), and ≥70 years of age for total knee arthroplasty (RR, 0.40 to 0.80). Age cohorts associated with an increased risk of prolonged postoperative opioid use were those ≥50 years of age for sports procedures (RR, 1.11 to 2.57) or total shoulder arthroplasty (RR, 1.26 to 1.40) and those ≥70 years of age for spine procedures (RR, 1.61). Identified risk factors for postoperative use were similar across subspecialties. Conclusions: We provide a comprehensive review of the various preoperative and postoperative risk factors associated with prolonged opioid use after elective and nonelective orthopaedic procedures. Increased BMI, prior substance abuse, psychiatric comorbidities, and chronic pain conditions were most commonly associated with prolonged postoperative opioid use. Careful consideration of elective surgical intervention for painful conditions and perioperative identification of risk factors within each patient's biopsychosocial context will be essential for future modulation of physician opioid-prescribing patterns. Level of Evidence: Prognostic Level IV . See Instructions for Authors for a complete description of levels of evidence.